QOL-60. PANACEA: A NOVEL BLACKBERRY 10 BASED, SUPPORT MOBILE APP FOR BRAIN TUMOR AFFECTED PATIENTS. Issue 2 (22nd June 2018) - Puri, Abhishek; Garg, Amit; Mohandass, P
Abstract: Panacea addresses a yawning gap in clinician-led development for novel use of mobile applications in healthcare delivery for patients. METHODS: Brain tumour affected patients have difficulty in accessing relevant literature to their clinical condition and reminders for medications. A novel BlackBerry 10 mobile app, Panacea, (final version 1.1.9.1) was conceptualised and developed (using C++ and BlackBerry 10 native SDK) available via BlackBerry World. BlackBerry 10 (OS version 10.3.2.2826) offers a platform with NIAP certification, which ratifies it for security allowing for unrestricted use for regulated healthcare. This app has news section (for patient advocacy), reminders to aid in dispensing of critical medications, ability to add emergency contacts and clinician vetted information for managing common side effects, primarily related to concurrent chemo-radiation therapy. This app also allows for visual theming, reader mode to enhance the readability of web content and sharing of news through various social media. Panacea is securely linked to installed BlackBerry Messenger (BBM), for instant messaging which also allows voice and video interaction with the clinical specialist. Future updates include enhanced heuristics (UI design with emphasis on the visual component), interface with hospital-based information systems, daily log of symptoms experienced and integration with chatbots for measured automated responses to repetitive queries. Porting to Android and Apple iOS platform is being contemplated. Panacea aims to transform information access with clinician vetting to aid in ownership of healthcare, functional independence and remote monitoring of patients.